UJI EFEK EKSTRAK ETANOL DAUN SALAM (Syzygiumpolyanthum) SEBAGAI DIURETIKA PADA TIKUS PUTIH JANTAN - Kesaktian Manurung; Novarianti Marbun; Salomo Joseph Empindonta (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
Bay leaf is a plant that one of its benefits is as a diuretic. Diuretics are drugs that act directly on the kidneys and increase the excretion of urine and sodium salts. The aim of the study was to determine the diuretic effect of ethanol extract of bay leaf (EEDS) on male white rats. The study used 25 male white rats, divided into 5 treatment groups: negative control group (CMC suspension 0.5%), positive control (furosemide suspension at a dose of 3.6 mg/kg BW), and a test group EEDS suspension at a dose of 100 mg/kg. BW, 200 mg/kg BW and 300 mg/kg BW. The test preparation was given orally to rats and then observed in a modified metabolic cage for 6 hours. The results of simplicia phytochemical screening showed positive for flavonoids, saponins and tannins. The results of EEDS characterization included a total ash content of 3.66%, water-soluble extract content of 3.69%, and ethanol-soluble extract content of 3.65%. The results showed that EEDS at a dose of 300 mg/kg BW showed the best diuretic effect compared to 200 mg/kg BW and 100 mg/kg BW, but the effect was lower than S. Furosemide 3.6 mg/kg BW. The results of the ANOVA EEDS test at doses of 100, 200 and 300 mg/kg BW had significant differences.